Change, leadership and change-oriented leadership theories in higher education: A review - Ghasemy, M.; Hussin, S. (2014)
Universities in 21st century are playing an important role in fostering the next generations of leaders who would be capable of dealing with significant economic, social, cultural and environmental challenges. However, higher education institutions need to be sustainably developed in order to have the potentials to contribute to the development of the societies as well. This shows that major changes must be planned, implemented and maintained in the context of higher education to transform the universities to the entities which can operate in the turbulent environment effectively and efficiently. Thus, the practical application of relevant theories of change and leadership in higher education institutions is pivotal to achieve this objective. Based on this view, the current paper aims to review a few theories of leadership and change which are pertinent to the context of higher education, and to discuss the characteristics of change-oriented leadership as well as to posit that change-oriented leadership may be the best suited leadership style which can be applied in higher education institutions in the turbulent environment of 21st century.